Implementation of the Hanifida Method as a Technique for Memorizing Asmaul Husana at the At-Taqwa Al-Qur'an Education Park (TPA), Pulau Harapan Village, Sembawa - Muthmainnah , Muthmainnah; Firmansyah, Firmansyah; Pehlic, Izet (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2025)
In developing religious values that are centered on monotheism, one of them is learning Asmaul Husna. Asma Al-Husna which has a fairly large number requires an appropriate method in understanding and memorizing Asmaul Husna. The Hanifida Method is a method that uses a combination system to memorize something. In practice, the object of memorization is associated with a word or sentence that is easy and familiar to someone's ears and mind, so that it can be easily digested and understood. This study aims to introduce the Hanifida Method and analyze how the application of this method has an impact on the process of memorizing Asma Al-Husna at the TPA At-Taqwa, Pulau Harapan Village, Sembawa. This study uses a qualitative approach with a descriptive research method, data collection techniques using observation and documentation techniques. The data analysis techniques used are data reduction, data verification and also providing conclusions. This study was conducted at the TPA At-Taqwa, Pulau Harapan Village, Sembawa. Based on the results of this study, the method applied to children went well and effectively. By using this method, they can not only memorize the words of Asma Al-Husna, but also memorize the meaning and its sequence number . The implications of applying the Hanifida Method to students at TPA At-Taqwa have a significant impact on improving the ability to memorize Asmaul Husna. The recommendation from the results of this study is to conduct comprehensive training for TPA and Madrasah Diniyah teachers so that they can apply this method optimally, and develop structured learning modules that are adjusted to various age levels of students.